Morphological inflectional rules for Karelian Proper verbs - Krizhanovskaya, Natalia; Novak, Irina; Krizhanovsky, Andrew; Pellinen, Nataliya (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2022)
A methodology for the development and implementation of inflectional rules for verbs in Karelian Proper is presented. The materials for this study were lemmas and word forms from the Open corpus of Veps and Karelian languages (VepKar) and the electronic version of the Karelian language Dictionary. The system of rules for automatic verb inflection for the Karelian Proper supradialect is of both practical and theoretical scientific interest. The new rules have already enabled entering 141 000 Karelian Proper word forms in the VepKar dictionary. The new program for word form generation has significantly reduced the time for adding the full inflectional paradigm of any Karelian Proper verb to the VepKar dictionary. One only needs to fill in several template parameters instead of 125 word forms. Kokkuvõte. Natalia Krizhanovskaya, Irina Novak, Andrew Krizhanovsky, Nataliya Pellinen: Morfoloogilised muutereeglid päriskarjala verbide jaoks. Artiklis esitletakse metodoloogiat, mida kasutati muutereeglite väljatöötamisel ja rakendamisel päriskarjala verbide jaoks. Materjali moodustasid vepsa ja karjala keele avatud korpusest (VepKar) ning karjala keele sõnaraamatu elektroonilisest versioonist kogutud lemmad ja sõnavormid. Esmakordselt arendati välja reeglite süsteem päriskarjala verbivormide automaatseks genereerimiseks. See on teaduslikult huvipakkuv nii praktilise kui ka teoreetilise poole pealt. Uued reeglid on juba võimaldanud lisada 141 000 päriskarjala sõnavormi VepKar sõnaraamatusse. Uus sõnavormide genereerimise programm on oluliselt vähendanud aega, mis kulub täieliku muuteparadigma lisamisele mingi päriskarjala verbi juurde Vepkar sõnaraamatus. 125 sõnavormi asemel on selleks üksnes vaja täita mallid mõningate parameetritega.